PERAN KANTOR WILAYAH PROVINSI JAMBI DALAM PENYELESAIAN SENGKETA PERTANAHAN MELALUI MEKANISME MEDIASI - Sigit Somadiyono (Universitas Batanghari Jambi, 2018)
Mediation is one of the ways to resolve the issue of non litigation, where the parties sit together facilitated by the mediator which is in this study was conducted by Regional Office of National Land Agency of Jambi Province. The issue appointed by this research is how is the type of line dispute settled through the mediation path in Regional Office of National Land Agency of Jambi Province and how is the role of Regional Office of National Land Agency of Jambi Province in the settlement of land disputes through mediation mechanisms. The purpose of this research is to find out what type of case that is requested by mediaton to Regional Office of National Land Agency of Jambi Province and the role of Regional Office of National Land Agency of Jambi Province in process of the mediation.Keywords: content, formatting, article